2013
DOI: 10.1177/0899764013481111
|View full text |Cite
|
Sign up to set email alerts
|

National Styles of NGO Regulation

Abstract: Why do Organisation for Economic Cooperation and Development (OECD) countries vary in their regulatory approach toward nongovernmental organizations (NGOs)? This article introduces an index to assess NGO regulation regarding barriers to entry, NGOs’ political capacity, and economic activity. Our cross-section analysis of 28 OECD countries offers preliminary evidence of systematic differences in NGO regulation between corporatist and pluralist systems. We suggest corporatist systems have more restrictive regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…In addition, government funding for CSOs in the region might be tempered by increasingly restrictive policies, which influence barriers to entry, limitations in political engagement, and restrictions related to economic activates for CSOs (Bloodgood et al, ). Recent research on restrictive policies in the Andean region found that Bolivia, Ecuador, Colombia, and Peru have all experienced the implementation of policies which are perceived by CSOs as weakening civil society spaces and funding sources (Appe and Barragán, forthcoming b ).…”
Section: New Revenue Sources and Modes Of Self‐financingmentioning
confidence: 99%
“…In addition, government funding for CSOs in the region might be tempered by increasingly restrictive policies, which influence barriers to entry, limitations in political engagement, and restrictions related to economic activates for CSOs (Bloodgood et al, ). Recent research on restrictive policies in the Andean region found that Bolivia, Ecuador, Colombia, and Peru have all experienced the implementation of policies which are perceived by CSOs as weakening civil society spaces and funding sources (Appe and Barragán, forthcoming b ).…”
Section: New Revenue Sources and Modes Of Self‐financingmentioning
confidence: 99%
“…This may be due to obstacles stemming from additional internal factors, such as the staff's demographics, experiences, or training. It also could be due to obstacles in the non-governmental organization's institutional environment (Bloodgood, Tremblay-Boire, and Prakash 2014) or its interactions with states, IGOs, donors, and other actors (Carpenter 2014). The book does not specify when an organization's managerial structure will provide it enough power to overcome constraints in the overall institutional environment.…”
Section: Internal Traitsmentioning
confidence: 99%
“…The regulation of organizations centres on processes of legalization, rules related to political activity and oversight on financial resources (Bloodgood et al ., ). Organized civil society in Ecuador has sought to shift from a reliance on government regulation to sector‐level self‐regulation.…”
Section: Discussion: Shifting the Development Discoursementioning
confidence: 97%